Development and Initial Validation of a Social Media Identity Distress Scale Among Emerging Adults. (3rd July 2021) - Luo, Ye; Watson, Joshua C.; Lenz, A. Stephen
Abstract: This study provided preliminary evidence for a new Social Media Identity Distress Scale (SMIDS) using two subsamples of emerging adults (18-25 years of age) from Amazon Turk (each n = 373). The factor analysis revealed a single-factor scale explaining 72.9% of the variance in the items and supported a 20-item version of the original 66-item instrument. The evidence of convergent validity and reliability supported using the SMIDS as a potential instrument to evaluate the mental stress regarding the ability to create a coherent self-concept while engaging in social media activities experienced by emerging adults. Implications for practice and future directions of research are provided.